OPTIMIZATION OF R-FACTOR AT GRAPPA PARALLEL ACQUISITION TECHNIQUE ON THE IMAGE INFORMATION T2 AXIAL BRAIN MRI - Saifudin Saifudin; Hermina Sukmaningtyas; Rini Indrati; Aris Santjaka (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: GRAPPA or Generalized Auto-calibrating Partially Parallel Acquisitions is a parallel acquisition technique which can reduce the scan time in MRI examination. Aims: This study aims to investigate the effect of the R-factor variation of GRAPPA on image anatomical information quality and to determine the optimization value of GRAPPA e-factor to fasten the scan time with acceptable image information quality. Methods: Eight respondents will perform T2 axial Brain MRI examination with various values of GRAPPA R-factor (1 to 7), evaluation was conducted with questionnaire which was given to 3 radiologists to assess the anatomical structure of the lateral ventricle, thalamus, caudate nucleus, lent form nucleus, internal capsule and background area. Data from respondents were then tested with Spearman test and Friedman test. Results: Statistics test showed that there was significant effect of GRAPPA parallel acquisition technique on the anatomical image information quality of T2 axial Brain MRI (p value of 0,001<0,05) and the correlation direction was negative, in which the higher the value of r-factor GRAPPA used, the lower the quality of anatomical image information. Based on the result of mean rank, image with optimal image anatomical information quality was image with GRAPPA R-factor of 1 (mean rank = 6.01), but image anatomical information quality with GRAPPA R-factor of 3 was acceptable with fast scan time (opinion of 75 % of all radiologists). Conclusion: R-factor at GRAPPA parallel acquisition technique could reduce scan time, but the higher the value of r-factor GRAPPA used, the lower the quality of image anatomical information.